The glass lake - Binchy, Maeve (New York : Dell, 1996)
A novel of a mother's secret and a daughter's courage, and their relationship that neither deceit nor death can destroy.
Library Journal
School Library Journal
Wilson's Fiction
Young Adult.
Young Adult
Keywords: Mothers and daughters -- Fiction; Mother-daughter relationship -- Fiction; Mystery fiction; Ireland -- Fiction; Ireland -- Fiction